Recombinant Immunotoxin with T Cell Epitope Mutations that Greatly Reduce Immunogenicity for Treatment of Mesothelin Expressing Tumors - Mazor, Ronit (Mol Cancer Ther, 2015)
SS1P is a recombinant immunotoxin (RIT) that targets mesothelin. It consists of an anti-mesothelin Fv fused to a portion of Pseudomonas exotoxin A. In clinical studies it has produced dramatic responses in patients with advanced mesothelioma, when combined with immunosuppressive therapy so that several treatment cycles could be given. Otherwise its activity is limited by its immunogenicity. In this work we describe the development and characterization of LMB-T20, a highly potent RIT targeted at mesothelin expressing cancers with low immunogenicity due to removal of its 8 T cell epitopes. LMB-T20 was more active than SS1P when tested on 4 different mesothelin expressing cell lines as well as on cells obtained from patients with mesothelioma. It also has potent anti-tumor activity in mice, and has reduced immunogenicity as measured by cytokine secretion assays. In conclusion, LMB-T20 is favorable candidate for evaluation in clinical trials due to its reduced immunogenicity and excellent activity.